THE CORRELATION BETWEEN STUDENTS’ ANXIETY AND SPEAKING SKILL AT STKIP KUSUMA NEGARA JAKARTA (A survey research first semester academic year 2018/2019) - Megawati Megawati (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2019)
The purpose of this research is to know whether there is any correlation between students’anxiety and speaking skill at STKIP Kusuma Negara Jakarta, first semester academic year 2018/2019.This research used quantitative method and the design was correlational research. The sample of this research consists of 25 students. The data of the students’anxiety were collected by using the questionaire which was adopted from foreign Language Classroom Anxiety Scale Horwitz et.at FLCAS, while the data of students’speaking skill were collected by using speaking test. In this research, researcher has two variables, independent variable which variable students’anxiety and dependent variable consists of students’ speaking skill.The researcher use SPSS program, before doing the analysis the data normality was tested by using Kolmogorf-Smirnov test to see if the population was distributed normal. The result of this research concluded that there is significant correlation between variable (X) students’anxiety and variable (Y) speaking skill. Sig. (2-tailed) is 0.001 < 0.05. It means that students who have higher speaking skill, they was influenced by anxiety. The value of correlation coefficient is -0.629 <0.5. It means that there is negative correlation between students’anxiety and speaking skill. If the students’anxiety is high so speaking skill is low and if the students’anxiety is low so speaking skill is high.